2021
DOI: 10.1155/2021/6621937
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Related Osteonecrosis of the Jaw Spontaneously Occurred in a Patient with Chronic Myelogenous Leukemia Only by Imatinib: A Report of a Rare Case

Abstract: The prevalence of medication-related osteonecrosis of the jaw (MRONJ) associated with molecular-targeted therapies such as bevacizumab and sunitinib has been constantly increasing in recent years. MRONJ frequently occurs after invasive dental procedures such as tooth extraction in patients currently or with a previous history of receiving antiresorptive agents including bisphosphonates and/or denosumab. Here, we report a rare case of spontaneously occurring MRONJ of the mandible in a 52-year-old Japanese woman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Beyond its impact on blood vessels, imatinib also influences bone remodeling processes. By inhibiting signaling through c-fms and c-kit, imatinib may lead to a reduction in both the number and activity of osteoclasts [20][21][22].…”
Section: Imatinibmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond its impact on blood vessels, imatinib also influences bone remodeling processes. By inhibiting signaling through c-fms and c-kit, imatinib may lead to a reduction in both the number and activity of osteoclasts [20][21][22].…”
Section: Imatinibmentioning
confidence: 99%
“…This treatment successfully alleviated his symptoms without the need to discontinue imatinib. Okubo-Sato et al [22] reported a case involving a 52-year-old woman who experienced exposed bone and pain upon contact in the right mandible following treatment with imatinib due to chronic myeloid leukemia (CML). She underwent sequestrectomy and had the mandibular tori removed.…”
Section: Imatinibmentioning
confidence: 99%